Polyester vascular prostheses — antibacterial and athrombogenic biomaterials. Part II. Effect of two-stage modification of polyester vascular prostheses on the selected physicochemical, mechanical and microbiological properties - Karaszewska, A.; Bucheńska, J. (Polimery, 2013)
The aim of this study was to examine the effect of two-stage modification of polyester vascular prostheses DALLONŽH on the physicochemical (changes in the electrokinetic charge of the surface, water permeability and hydrophilicity), mechanical (resistance to pin puncture) and microbiological (in vitro, in vivo) properties. The electrokinetic potential measurement showed that the modified vascular prostheses had negative electrokinetic charge which repels negatively charged protein particles and morphotic blood elements. Consequently, they fulfill the necessary condition to obtain a positive assessment of athrombogenicity (Table 2). The permeability and hydrophilic properties after the modification do not differ from those of commercially available standard prostheses (Table 3). It has been found (Table 4) that two-stage modification process does not impair the resistance to pin puncture. The in vitro tests (Table 5) have confirmed that the products containing amikacin are active in relation to Gram-positive and Gram-negative bacteria typical under hospital conditions (Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, P. aeruginosa ATCC 27853). Preliminary in vivo tests (Table 6) showed no irritating effect of the modified blood vessels prostheses.